Impact of wet cacao bean collection centers on the organizational, production, and entrepreneurial dynamics of producer cooperatives - Camacho Obando, Álvaro José; Centeno Zamora, Janira Damarys; López Lanzas, Donaldo; Laguna, Tomás; Godoy Gross, Ricardo (Catholic Relief Services, 2012)
This document compiles the results and lessons learned of the project “Alliance to Create Opportunities for Rural Development through Agro-enterprise Relationships” (ACORDAR), aimed to help increase the income, ensure permanent employment and strengthen the business capacities of 7000 poor rural households in 50 municipalities of Nicaragua. The document compiles the experiences of 897 families of small-scale women and men cacao producers.